2003
DOI: 10.1002/bdra.10075
|View full text |Cite
|
Sign up to set email alerts
|

Selection of normalizer genes in conducting relative gene expression analysis of embryos

Abstract: BACKGROUND In relative gene expression analysis, a reference gene for sample normalization is required for determining target expression changes among experimental treatment groups. Since some developmental toxicants secondarily cause general growth retardation and/or other general biological changes, commonly used housekeeping genes may not serve as accurate normalizers. METHODS We conducted real‐time polymerase chain reaction (PCR) with normalization to calculate relative target transcriptional change, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Mamo et al [33] showed moderate changes for the genes ACTB , GAPDH , HPRT1 and others in an in vitro and in vivo experiment at different stages using whole embryos. The cells comprising the embryo have a vastly heterogeneous nature, which leads to greater variation in the endogenous biological processes, and greater variation in the sensitivity of cells to their environment [34]. Because these factors can introduce intra- and inter assay variations, we elected to isolate the specific EH organs of interest (heart, liver, spleen, thymus) and analyze gene expression in these organs independently instead of analyzing whole embryo homogenates, as has been previously described [35].…”
Section: Discussionmentioning
confidence: 99%
“…Mamo et al [33] showed moderate changes for the genes ACTB , GAPDH , HPRT1 and others in an in vitro and in vivo experiment at different stages using whole embryos. The cells comprising the embryo have a vastly heterogeneous nature, which leads to greater variation in the endogenous biological processes, and greater variation in the sensitivity of cells to their environment [34]. Because these factors can introduce intra- and inter assay variations, we elected to isolate the specific EH organs of interest (heart, liver, spleen, thymus) and analyze gene expression in these organs independently instead of analyzing whole embryo homogenates, as has been previously described [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, embryonic samples have additional sources of variations. Unlike cell lines and single-organ tissues, the cells comprising the embryo have inherently a vastly heterogeneous nature, which leads to greater variation in the endogenous biological processes, and greater variation in the sensitivity of the cells to the treatment [16]. There is high probability that any of these factors can introduce intra- and inter assay variations for which normalization is required.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression level of the reference gene should be similar to that of the target gene. However, several recent studies have shown that, in vertebrate systems, the mRNA expression of reference genes differed among tissues, various cells, and after treatment (Zhang,2003; Bas et al,2004; de Kok et al,2004; Bustin and Nolan,2004; Vandesompele et al,2002; Brunner et al,2004; Radonic et al,2004). To date, the most reliable method for normalisation appears to relate the mRNA data to the total RNA content of the sample preparation subjected to the reverse transcription reaction (Bustin,2002).…”
Section: Introductionmentioning
confidence: 99%